Gambaran Penggunaan Obat Anti Epilepsi (OAE) pada Penderita Epilepsi Berdasarkan Tipe Kejang di Poli Saraf Rumkital DR. Ramelan Surabaya - Eric Hartono Tedyanto; Laurawati Chandra; Olivia Mahardhani Adam (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2020)
Epilepsy is a disorder of the central nervous system (CNS) characterized by attacks (seizures, fit, attack, spell) spontaneous (unprovoked) and periodically. The main treatment of epilepsy is with antiepileptic drugs.  It was used the descriptive study design by using secondary data which taken at Medical Record Installation of Dr. Ramelan Naval Hospital Surabaya from September-November 2018. The results showed that the percentage of focal seizures is 41%, seizures general is 36% and unclassified seizures is 23%. From 61 samples, the percentage of anti-epileptic drugs used are phenytoin (31.1%), valproic acid (21.3%) and carbamazepine (4.9%) as a monotherapy. While 42.7% were treated with polytherapy that the combination of phenytoin, valproic acid, carbamazepine and benzodiazepines. Focal seizure that dominate with 41%, the general seizure is 36% and unclassified  seizures is 23%. Anti-epileptic drugs that are widely used class of phenytoin, valproic acid and carbamazepine as monotherapy and the combination of phenytoin, valproic acid, carbamazepine and benzodiazepines as polytherapy.